Implementation of Physical Test Results Measurement Using a Volleyball Sports Web Application - Tampubolon, Katarina Boru; Hartati, Hartati; Destriani, Destriani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The Research entitled the application of measuring physical test results using a web application for junior high school students in the sport of volleyball, by Katarina Br Tampubolon. And supervised by Prof. Dr. Dra. Hj. Hartati, M. Kes and Destriani, M. Pd. This study aims to explain the category norms for measuring physical test results in volleyball using a web application. The components of physical condition that are very important in volleyball include strength, flexibility and endurance. This research is quantitative research with a descriptive research design. The sample for this research was 45 students in class VII of Indralaya 1 Public Junior High School, consisting of 30 students and 15 female students. Data collection was carried out using the following test instruments: the strength component used the 60 second sit up test and the 60 second push up test, the flexibility component used the v sit and reach test, and the endurance component used the 20 meter bleep test. The place of research was carried out at Indralaya 1 Public Junior High School. The results obtained from research on class VII students of Indralaya 1 Public Junior High School in volleyball for the average physical condition were in the very good category (0%), good category (0%), fair category (14%), poor category (46%). ) and very less category (20%). From all the categories above, it can be concluded that the average physical condition of class VII students at Indralaya 1 Public Junior High School is in the poor category with a percentage of 46%. This research is intended as material for evaluation and awareness for students to continue to improve and maintain their physical condition so that they can achieve maximum performance